Polysorbates prevent biofilm formation and pathogenesis of Escherichia coli O104:H4. Issue 9 (20th October 2016) - Sloup, Rudolph E.; Cieza, Roberto J.; Needle, David B.; Abramovitch, Robert B.; Torres, Alfredo G.; Waters, Christopher M.
Abstract: Escherichia coli biotype O104:H4 recently caused the deadliest E. coli outbreak ever reported. Based on prior results, it was hypothesized that compounds inhibiting biofilm formation by O104:H4 would reduce its pathogenesis. The nonionic surfactants polysorbate 80 (PS80) and polysorbate 20 (PS20) were found to reduce biofilms by ≥ 90% at submicromolar concentrations and elicited nearly complete dispersal of preformed biofilms. PS80 did not significantly impact in vivo colonization in a mouse infection model; however, mice treated with PS80 exhibited almost no intestinal inflammation or tissue damage while untreated mice exhibited robust pathology. As PS20 and PS80 are classified as 'Generally Recognized as Safe' (GRAS) compounds by the Food and Drug Administration (FDA), these compounds have clinical potential to treat future O104:H4 outbreaks.